Small scale model of deltatron based technique for high dc voltage generation / Mohd Zakir Zahri - Zahri, Mohd Zakir (1999)
High Voltage Engineering and related fields have become an integral part of our society and consequently its uses are widespread. This field still requires and even rigorous researches and investigations to be explored. One of related field in High Voltage Engineering is the High dc Voltage Generation. Generations of high dc voltages are mainly required in research work and have numerous other applications. This report concern on the discussion of high dc voltage generation by modeling cascade transformers incorporated with high dc voltage multiplier circuit popularly known as Deltatron. The complete system comprises a high frequency oscillator, low scale rectifier circuit, conventional step-up transformers, filter circuits and Cockcroft-Walton circuit acts as the voltage multiplier. The hardware set-up is also discussed especially the components involved. This technique has experimentally tested in the laboratory and its characteristic; include circuit stability and responses are emphasised in this report.